Your question is missing the figure, so the figure for your question is attached below:
Answer:
shade 2 strips out of 4 to get fraction strip equivalent to Mandy's fraction strip
Step-by-step explanation:
As Mandy shaded the 3 trips out of the total six strips. It shows the fraction of ![\frac{3}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B6%7D)
and
To shade the given fraction strip so that it represents a fraction that is equivalent to Mandy's fraction strip, we should shade 2 stripes out of 4 that is equivalent to
i.e. ![\frac{2}{4}=\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B4%7D%3D%5Cfrac%7B1%7D%7B2%7D)
My Fraction Strip is equivalent to Mandy's Fraction Strip because both are equal to
Answer:
1st ∡ = 15.5°
2nd ∡ = 77.25°
3rd ∡ = 87.25°
Step-by-step explanation:
1st ∡: x
2nd ∡: y
3rd ∡: z
Equations we can create from data given in problem:
y + z = 5x
z = 5x + 10
We have enough expressions to create an equation:
x + 5x + 5x + 10 = 180
11x = 170
x = 15.5
y = 5(15.5) = 77.25
z = y + 10 = 87.25
Answer:
5(x−1)(x+4)? i think
Step-by-step explanation:
Answer:
Seven one dollar bills and eight five dollar bills.
Step-by-step explanation:
8 + 7 = 15 bills
8 x 5 = $40
7 x 1 = $7
40 + 7 = $47
47 dollars and 15 bills.
Answer:
x ≈ -4.419
Step-by-step explanation:
Separate the constants from the exponentials and write the two exponentials as one. (This puts x in one place.) Then use logarithms.
0 = 2^(x-1) -3^(x+1)
3^(x+1) = 2^(x-1) . . . . . add 3^(x+1)
3×3^x = (1/2)2^x . . . . .factor out the constants
(3/2)^x = (1/2)/3 . . . . . divide by 3×2^x
Take the log:
x·log(3/2) = log(1/6)
x = log(1/6)/log(3/2) . . . . . divide by the coefficient of x
x ≈ -4.419
_____
A graphing calculator is another tool that can be used to solve this. I find it the quickest and easiest.
_____
<em>Comment on alternate solution</em>
Once you get the exponential terms on opposite sides of the equal sign, you can take logs at that point, if you like. Then solve the resulting linear equation for x.
(x+1)log(3) = (x-1)log(2)
x=(log(2)+log(3))/(log(2)-log(3))